ANALISIS DEIKSIS CERPEN REMBULAN DI MATA IBU KARYA ASMA NADIA - Nuraeni, Lia; Siagian, Irwan; Hasanah, Uswatun; Astuti, Yulia Dini; Nugroho, Rudiyanto Sapto (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Deixis is included in the study of pragmatics which is a link between the structure of language and the context of the situation used. The use or phenomenon of deixis usually appears in dialogs between characters in literary works including short stories. The research entitled